University Students’ Attitudes & Perspectives on Sustainability in Sarawak - Chelsea, Michcal; Mohd Hasnain, Hussain (2022)
Abstract: Within the recent decades, there is an emerging trend in higher education as curriculum and administration seek to incorporate the goals of sustainability and development. In Malaysia, a lot of campus-based initiatives that seek to forward the goals of sustainable development also took off. The purpose of this paper is to explore the extent of a public or private university student’s knowledge on sustainable development and the United Nation (UN) Sustainable Development Goals (SDGs). The objective of the study is to analyze the outcome of the perceived knowledge on student behavior. It also tries to examine the manners in which students can contribute towards sustainable development efforts given the challenges and obstacles they currently face. In this research, a qualitative method was employed to evaluate students’ attitudes and perspectives on sustainability in a public and private university in Kuching. An in-depth interview was held with students from both universities. The selected interviewees consist of students who possessed the authority to speak on the issue and on behalf of their peers. Students’ knowledge and the ability to transform the knowledge into practice are the focal concern of the in-depth interview. The result of the interview shown that students are generally aware of the concept of sustainable development and the contemporary issues related to it. They were also able to articulate the inclusion of the UN SDGs in their campus life such as in their curricular or extracurricular activities. However, there were a few differing opinions on the adequacy of sustainable behaviors and the ongoing efforts done to address sustainability issues.